Preparedness of Elderly in The Disaster-Prone Area of Mount Merapi, Sambung Rejo, Balerante - Nurhidayati Istianna; Agustiningrum Ratna; Sulistyowati Arlina Dhian; Regmi Anil Babu; Zukhri Saifudin; Hastuti RetnoYuli; Winarti Ambar; Asmarani Jasita Putri (E3S Web of Conferences)
The eruption of Mount Merapi caused extensive damage and loss in Klaten Regency. The most vulnerable members of society, notably the elderly, are most likely to become victims of natural disasters. The goal of this research was to determine the significance and relevance of the elderly’s experiences during the Mount Merapi disaster. The study used a qualitative approach, with a descriptive phenomenological technique, to assist researchers understand the picture of senior ready. This research had a population of 22. The sample approach used in this investigation was purposeful sampling. Recruiting participants for qualitative research based on inclusion criteria and collecting data via in-depth interviews, observations, and field notes. The number of participants required to achieve saturation was seven. Ten themes will be discussed in this study : (1) Knowledge about the risks of living in a disaster-prone area III, (2) The impact of Mount Merapi’s eruption, (3) Emergency Response Plan, (4) Temporary shelter, (5) Evacuation flow, (6) Information sources, (7) Health Problems, (8) Health Facilities in Refugees, (9) Disaster Preparedness, and (10) Hopes of the Elderly for Officers. This study concludes that older persons in disaster-prone area III are a vulnerable population that should be prioritized. The elderly of Sambungrejo hamlet are already familiar with disaster preparedness procedures.